2016
DOI: 10.1007/s11060-016-2078-0
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible encephalopathy syndrome in cancer patients: a single institution retrospective study

Abstract: Posterior reversible encephalopathy syndrome (PRES) is a clinico-radiologic entity. Its management and outcome in the oncology population is limited because it is still difficult to identify despite an increasingly recognized occurrence. This is the largest retrospective study of PRES in cancer patients reported from a single institution. We explore the clinical manifestations and radiologic features to comprehensively assess PRES in order to prevent permanent neurologic deficits and mortality. We retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…We found that the majority of cases of PRES were recorded after a cycle of chemotherapy, as recently observed in cancer adult patients. 14 This must be stressed, because it configures this syndrome as a relatively common complication in the clinical practice of hematologyoncology pediatrician, not exclusively related to HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the majority of cases of PRES were recorded after a cycle of chemotherapy, as recently observed in cancer adult patients. 14 This must be stressed, because it configures this syndrome as a relatively common complication in the clinical practice of hematologyoncology pediatrician, not exclusively related to HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In most situations, patients with unfavourable outcomes are more frequently seen in state of neurotoxicity such as chemotherapy, sepsis and frequently have serious underlying medical conditions, such as neoplasm, autoimmune disease or infection/sepsis/shock. However, elimination of these neurotoxic states may be difficult in such challenging clinical settings 53. However, a delay in the elimination of the causative factor may also represent an important predictor of poor outcome, which might further explain the seemingly worse prognosis of these patients 54.…”
Section: Prognosismentioning
confidence: 99%
“…However, in addition to secondary CNS manifestation and HSV-1 related vasculitis, there are further causes of neurological deterioration in SMZL. Posterior leukoencephalopathy syndrome and vasoconstriction syndrome are clinical mimics of encephalitis, that show vascular alterations and has been reported in the context of lymphoma and with the oncological therapies used in our patient [42,43]. Ibrutinib, a Bruton's tyrosine kinase inhibitor, has been increasingly widely used in relapsed and refractory SMZL.…”
Section: Discussionmentioning
confidence: 54%